Money, markets, and trade in early Southeast Asia the development of indigenous monetary systems to AD 1400 - Wicks, Robert S (Studies on Southeast Asia, 1992)
Money places an explicit value on all things and this work by Robert S. Wicks explores the impact of monetization in premodern Southeast Asia from the third century BC to the rise of Maleka in the early fifteenth century. Ideas about money developed unevenly throughout the region and the author, in seven case studies written in a highly narrative style, explores why this was so. He considers trade policies, price controls, exchange ratios, monopolies, variant standards of value, and the administrative complexity necessary for such economic complexity. Reproduced data, maps, tables, and figures display the intertwining of anthropology, archeology, history, culture, and economics.